(untitled) (Research, Society and Development, 2020)
Sexual violence in women today is still considered a subject full of taboos and prejudices by society, and is characterized by sexual acts without the permission of the victim, in most cases is accompanied by physical force, psychological pressure, or even serious threat. This study aims to analyze the profile of women victims of sexual violence in Brazil. It is a study of integrative revision of the literature, of the descriptive type with qualitative approach. The Virtual Health Library (VHL); Scientific Electronic Library Online (SCIELO), and Periódicos CAPES, databases were used. Through the results and survey of information it was found that young adult women are more likely to be victims of sexual violence, other factors that may influence the practice of this crime are related to marital status, schooling, race/color, drinking alcohol and the COVID-19 pandemic, because it is worsening this reality experienced by women. In view of the above, it is necessary to have a strengthening of public policies aimed at assisting victimized women to avoid sexual violence.